Government of Jammu and Kashmir Draft Annual Plan 1982-83 Volume VII - Government of Jammu and Kashmir (Government of Jammu and Kashmir, 1981)
The Draft Annual Plan 1982-83 for Jammu and Kashmir presents a comprehensive framework for development across education, health, technical education, arts and culture, water supply, sanitation, and employment generation. In general education, the plan emphasizes increasing enrollment, opening new schools, upgrading facilities, and improving teacher-student ratios, with a proposed allocation of Rs. 75 lakhs for construction and staffing of 100 additional schools. Arts and culture initiatives focus on preserving heritage, promoting local crafts, and enhancing infrastructure such as the Dogra Art Gallery. Technical education aims to modernize institutes, introduce new courses, improve laboratories, and strengthen industry linkages with Rs. 45 lakhs allocated for expansion and quality enhancement. Health and medical infrastructure improvements include expansion of district hospitals and PHCs, establishment of a combined food and drug laboratory, procurement of essential medical equipment, and upgradation of Primary Health Centres in R.S. Pura and Kot Bhalwal, with a total outlay of Rs. 628.80 lakhs. Water supply and sanitation plans prioritize rural and urban coverage, targeting 100% population access by 1996, with significant allocations for new schemes and infrastructure maintenance. Employment generation and social welfare programs aim to support marginalized communities, including Gujjars and Bakerwals, through skill development, entrepreneurship, vocational training, and housing initiatives. Agricultural productivity is addressed via irrigation projects, livestock development, and cooperative support programs. Overall, the plan integrates strategic financial allocations, targeted staffing, and programmatic initiatives to foster socio-economic upliftment, improve public services, and ensure inclusive development, reflecting a balanced approach to immediate needs and long-term growth in Jammu and Kashmir.
Planning and Development Department Jammu November, 1981
Planning and Development Department Jammu November, 1981
Keywords: Jammu and Kashmir; State Annual Plan; Education; Health; Technical Education; Arts and Culture; Water Supply; Employment Generation; Social Welfare; Rural Development; Irrigation; Medical Infrastructure